Chloride induced corrosion durability of high volume fly ash concretes containing nano particles - Shaikh, Faiz; Supit, S. (ELSEVIER SCI LTD, 2015)
This paper presents experimental results on chloride induced corrosion and related durability properties such as chloride permeability, water sorptivity, chloride diffusion and porosity of ordinary concrete and high volume fly ash (HVFA) concretes containing nano silica (NS) and nano calcium carbonate (NC) particles as partial replacement of cement. The NS and NC are used as 2% and 1%, respectively by wt. of cement in the above concretes. Results show that the addition of NS and NC significantly improved the corrosion resistance of ordinary concrete and HVFA concretes in terms of lower corrosion currents, lower steel loss and longer time require to create corrosion induced crack. Sorptivity, chloride diffusivity and chloride permeability of above concretes also reduced significantly due to the addition of NS and NC, which correlate well with the corrosion tests. The addition of NS and NC also significantly reduced the capillary pores and gel pores of above concretes and also shifted the pore concentration towards the medium capillary pores. Thermo gravimetric analysis (TGA) and differential thermal analysis (DTA) of above concretes also confirms the reduction of calcium hydroxide (CH) in the concretes containing nano particles, thus the formation of additional calcium–silicate–hydrate (CSH) gel in the system.